The Effect of Sustainable Dairy Cattle Value Chain Management Practices on Farmers’ Income in Kikatsi Subcounty, Kiruhura District (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The study focused on evaluating the effect of sustainable dairy cattle value chain management practices on farmers' income in Kikatsi Subcounty, Kiruhura District. It was guided by one objective to identify the factors influencing the adoption of sustainable dairy cattle value chain management practices in Kikatsi Subcounty. The study employed a cross-sectional research design. Primary data were collected from 238 respondents using a questionnaire and an interview guide. The study employed simple random sampling and purposive sampling to select the correct categories of respondents. The data was analysed using SPSS version 23.0. Results revealed that the adoption of sustainable dairy cattle value chain management practices in Kikatsi Subcounty is mainly driven by technological and input access, education level, access to credit facilities, institutional and extension support, farmers’ income, and market accessibility, all of which showed positive and significant effects. This indicates that when farmers have access to improved technologies, financial resources, education, and reliable markets, they are more likely to embrace sustainable dairy practices. The results explain that improvements in milk yield and quality, market access and prices, cost reduction through efficient resource use, and improved breeding and animal health significantly raise farmers’ earnings. The study recommends that; agricultural extension officers and cooperatives should intensify farmer training on sustainable feeding, breeding, and milk handling practices to sustain and expand gains in yield and quality. Policymakers should integrate sustainable dairy value chain practices into national agricultural programs, emphasizing incentives for farmers who adopt environmentally friendly and resource-efficient systems.